Komunikasi Interpersonal Keluarga Beda Agama dalam Penanaman Nilai Toleransi di Desa Sukoreno - Chaliq Putra, Ari Asisaka; Raudhatul Jannah, Siti; Usuluddin, Win (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine how interpersonal communication in families consisting of members of different religions, especially the relationship between children and parents in Sukoreno Village, Umbulsari District. This study uses a qualitative approach with in-depth interview methods and observations of the families of Resource Person A and Resource Person B as the main informants. The results of the study indicate that interpersonal communication carried out through dyadic and triadic communication plays an important role in instilling an attitude of tolerance and maintaining family harmony despite religious differences. There are obstacles in the communication process related to differences in beliefs, which can be overcome through habit, patience, and mutual respect. Parents not only convey messages verbally but also provide positive examples in maintaining tolerance. This study confirms that effective interpersonal communication is the main key to creating a harmonious and harmonious family atmosphere in the context of religious diversity. These findings provide an important contribution to understanding the dynamics of interfaith family communication and strategies for building tolerance in family life.